2021
DOI: 10.1101/2021.01.18.427058
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neuroprotective derivatives of tacrine that target NMDA receptor and acetyl cholinesterase - Design, synthesis and biological evaluation

Abstract: The complex and multifactorial nature of neuropsychiatric diseases demands multi-target drugs that can intervene with various sub-pathologies underlying disease progression. Targeting the impairments in cholinergic and glutamatergic neurotransmissions with small molecules has been suggested as one of the potential disease-modifying approaches for Alzheimer’s disease (AD). Tacrine, apotent inhibitor of acetylcholinesterase (AChE) is the first FDA approved drug for the treatment of AD. Tacrine is also a low affi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 95 publications
(143 reference statements)
1
6
0
Order By: Relevance
“…It is not known if tacrine and/or its metabolites are excreted in the bile or if they are transported via the enterohepatic system. The clearance of tacrine, however, does not appear to be affected by renal impairment [9,15,21]. [24].…”
Section: Overview Of Tacrinementioning
confidence: 94%
See 4 more Smart Citations
“…It is not known if tacrine and/or its metabolites are excreted in the bile or if they are transported via the enterohepatic system. The clearance of tacrine, however, does not appear to be affected by renal impairment [9,15,21]. [24].…”
Section: Overview Of Tacrinementioning
confidence: 94%
“…It was first used in clinical practice to treat anesthetic-induced delirium and to enhance the muscle-relaxing effects of succinylcholine [13]. It was first thought that tacrine would help counteract the respiratory depression caused by morphine; however, it was later revealed that it also acted as an inhibitor of both AChE and butyrlcholine esterase (BChE) [9,14]. In 1993, tacrine became the first medicine to be licensed for the treatment of Alzheimer's disease; however, its hepatotoxicity limited its usage [1].…”
Section: Overview Of Tacrinementioning
confidence: 99%
See 3 more Smart Citations